Performance Analysis of Efficient Energy Management in Routing Protocol for Mobile Wireless Sensor Network - B, Anil Kumar; Rao, K Ramkee (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless Sensor Networks (WSN) are promising and very appealing technology applied to different applications. Nodes(sensors) of a wireless sensor networks (WSNs) are powered by exhaustible batteries with limited life span and generally they are non-rechargeable. As the deployment of these WSNs occurs in harsh areas generally inaccessible and sometimes hostile, the replacement of depleted batteries is not feasible, so nodes must therefore ensure their mission with their unique initial strict energy budget. This constraint makes the energy resource the most decisive and of critical importance in the WSNs. The routing protocols have to pay much attention in this context of energy conservation. Cluster based routing protocols have significant impact on the energy dissipation and life time of wireless sensor networks (WSN). In this paper the proposed technique PEGASIS-MAEM(PEGASIS- Mobile average energy based) protocol for Multi hop network will be achieved by combining LEACH-MAE[1] based protocol with PEGASISMH[2]] protocol. This novel technique overcomes the pitfalls in present protocols and gives better mobile average energy based Cluster Head selection. All the simulations are carried out in NS2 simulator. Simulation results shows that our proposed protocol PEGASIS-MAEM outperforms compared to the other protocols.